Parental Social Status and Intrasexual Competitiveness among Adolescents. (29th April 2014) - Buunk, Abraham P.; Stulp, Gert; Ormel, Johan
A study among 1, 881 adolescents (52.3% girls) with a mean age of 19.1 years examined the effects of parental social status upon intrasexual competitiveness. Whereas females were consistently more intrasexually competitive the higher the socio-economic status of their parents, males with parents of the lowest socio-economic status tended to be more intrasexually competitive than those with parents of medium socio-economic status, and nearly as intrasexually competitive as those with parents of high socio-economic status. Only among adolescents with parents of low socio-economic status were males more intrasexually competitive than females. Among males and females, higher levels of intrasexual competitiveness were related to a higher family income, to a higher occupational status of the father as well as of the mother, and to a higher educational level of the mother. Only among females were higher levels of intrasexual competitiveness associated with a higher educational level of the father. Males whose fathers had only elementary education had a relatively high level of intrasexual competitiveness. The results are discussed in the context of the multifaceted nature of human status, and the potential relevance of intrasexual competitiveness for individuals of high versus low social status.